The rapid development of AmboVent: a simple yet sustainable ventilation solution for use in a pandemic. - Meiry, Gideon; Alkaher, David; Mintz, Yoav; Eran, Yuval; Kohn, Aryeh; Kornblau, Giora; Shneorson, Zeev; Alkaher, Shlomo; Sonkin, Roman; Jaffe, Eli (Minimally Invasive Therapy & Allied Technologies, 2022)
COVID-19 (SARS-CoV-2) emerged at the end of 2019, generating a rapidly evolving pandemic, raising serious global health implications. Among them was the fear of a mechanical ventilator shortage due to COVID-19's high contagion rate and pathophysiology. Fears of a ventilator shortage unleashed a wave of innovations. This manuscript describes the AmboVent, a ventilator, rapidly developed with a sense of urgency, by a group of Israeli volunteers. Using a decentralized approach, we worked extensively and managed within ten days to create a working ventilator. It utilizes a 64-year-old technological concept, the bag valve mask (BVM), sometimes known by the proprietary name Ambu bag, which we transformed into an automatic, controlled, and feature-rich ventilator by endowing it with contemporary computing technology. Applying a functional rather than a commercial-oriented approach can result in the ad hoc development of lifesaving solutions during a rapidly spreading pandemic.